Transcriptome Profiling of Buffalograss Challenged with the Leaf Spot Pathogen Curvularia inaequalis - Amaradasa, Bimal S.; Amundsen, Keenan (Frontiers in Plant Science, 2016)
Buffalograss (Bouteloua dactyloides) is a low maintenance U. S. native turfgrass species with exceptional drought, heat, and cold tolerance. Leaf spot caused by Curvularia inaequalis negatively impacts buffalograss visual quality. Two leaf spot susceptible and two resistant buffalograss lines were challenged with C. inaequalis. Samples were collected from treated and untreated leaves when susceptible lines showed symptoms. Transcriptome sequencing was done and differentially expressed genes were identified. Approximately 27 million raw sequencing reads were produced per sample. More than 86% of the sequencing reads mapped to an existing buffalograss reference transcriptome. De novo assembly of unmapped reads was merged with the existing reference to produce a more complete transcriptome. There were 461 differentially expressed transcripts between the resistant and susceptible lines when challenged with the pathogen and 1552 in its absence. Previously characterized defense-related genes were identified among the differentially expressed transcripts. Twenty one resistant line transcripts were similar to genes regulating pattern triggered immunity and 20 transcripts were similar to genes regulating effector triggered immunity. There were also nine up-regulated transcripts in resistance lines which showed potential to initiate systemic acquired resistance (SAR) and three transcripts encoding pathogenesis-related proteins which are downstream products of SAR. This is the first study characterizing changes in the buffalograss transcriptome when challenged with C. inaequalis.